Formulasi Sediaan Krim Menggunakan Kolagen Tulang Itik Serati (Cairina Moscahta) Sebagai Anti Aging - Nilsya Febrika Zebua; Nurul Anggraini; Sudewi Sudewi (Journal of Pharmaceutical and Health Research, 2020)
At the age of 30, humans lose about 15-20% of collagen and at the age of 40, humans no longer produce collagen, so additional collagen is needed from outside the body. Serati duck bone (Cairina moschata) has not been treated yet and is a waste. This study aims to determine the presence of collagen content in serati duck bones (Cairina moschata) and to formulate serati duck collagen in cream preparations as anti-aging. This study used an experimental method, using serati duck test material (Cairina moschata). Stages of research include extraction of collagen from serati duck bone (Cairina moschata), characterization of collagen with Infrared Spectrophotometry, manufacturing of serati duck bone collagen cream (Cairina moschata) with concentrations of 1%, 1.5%, 2.5%, 3.5% and evaluation of collagen cream preparations. The results showed that the serati duck bone (Cairina moschata) contained collagen at wave numbers 2920-3280 cm-1 and 1270 - 1630 cm-1 indicating the presence of amine and amide groups. Serati duck collagen can be formulated into an oil-emulsion (M / A) type of cream emulsion with the results of evaluation of the preparation is a homogeneous and stable preparation for 12 weeks of storage, does not irritate the skin, and the pH range of 6.0 to 6.3. Statistical test results show a probability smaller than 0.05. The results of the test of anti-aging cream preparations on the face showed changes in large pores to small, changes in many blemishes to a little and changes in wrinkled skin to become wrinkled. Anti aging cream preparations have shown a significant increase in effect every week for a month using this anti aging cream